Da'wah on new media and religious authorities in Indonesia - Naamy, Nazar (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2023)
Purpose - The purpose of this research is to find out the art and management of Ustadz Syam's da'wah in the TikTok account from the analysis of the sociology of da'wah.Method - This research uses a netnographic approach that focuses on the art and sociology of da'wah Ustadz Syam on the TikTok account.Result - The results showed that religious authority is not only controlled by traditional da'i who have a scientific base in pesantren, but now new authority is born from those Da'is who are close to new media, content, packaging, fashion, and social media platforms to preach.Implication - The da'wah movement that needs to be carried out in the future should adapt to the dynamics of the times and in accordance with the needs of the wider community..Originality - This research is related to the application of da'wah in TikTok, Ustadz Syam presents a new authority as a challenge to the old Da'i who need to care about popular media platforms.***Tujuan - Tujuan dari penelitian ini adalah untuk mengetahui seni dan manajemen dakwah Ustadz Syam di akun TikTok dari analisis sosiologi dakwah.Metode - Penelitian ini menggunakan pendekatan netnografi yang berfokus pada seni dan sosiologi dakwah Ustadz Syam di akun TikTok.Hasil - Hasil penelitian menunjukkan bahwa otoritas keagamaan tidak hanya dikuasai oleh da'i tradisional yang memiliki basis keilmuan di pesantren, namun kini otoritas baru lahir dari para da'i yang dekat dengan media baru, konten, kemasan, fashion, dan platform media sosial untuk berdakwah.Implikasi - Gerakan dakwah yang perlu dilakukan di masa depan harus menyesuaikan dengan dinamika zaman dan sesuai dengan kebutuhan masyarakat luas.Orisinalitas - Penelitian ini terkait dengan penerapan dakwah di TikTok, Ustadz Syam menghadirkan otoritas baru sebagai tantangan bagi para Da'i lama yang perlu peduli dengan platform media populer.